Log in to add a comment

## Answers

For cubing a binomial we need to know the formulas for the sum of cubes and the difference of cubes.

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Example:

( x + y ) ³ = ?

Step 1: Cube the 1st term.

Step 2: Square the 1st term, multiply it to the 2nd term, finally, multiply by 3.

Step 3: Square the 2nd term, multiply it to the first terms, finally, multiply by 3.

Step 4: Cube the 2nd term.

Step 5: Combine the results of your steps and reduce if necessary.

Cube the binomial:

( x + y ) ³

Step 1: Cube x.

= x³

Step 2: Square x, multiply by y, then multiply by 3.

= 3x²y

Step 3: Square y, multiply by x, then multiply by 3.

= 3xy²

Step 4: Cube y.

= y³

Step 5: Combine your initial answers and reduce if necessary.

= x³ + 3x²y + 3xy² + y³

Answer:

The cube of the binomial ( x + y ) or ( x + y ) ³ is

= x³ + 3x²y + 3xy² + y³

( x + y ) ³ = ?

Step 1: Cube the 1st term.

Step 2: Square the 1st term, multiply it to the 2nd term, finally, multiply by 3.

Step 3: Square the 2nd term, multiply it to the first terms, finally, multiply by 3.

Step 4: Cube the 2nd term.

Step 5: Combine the results of your steps and reduce if necessary.

Cube the binomial:

( x + y ) ³

Step 1: Cube x.

= x³

Step 2: Square x, multiply by y, then multiply by 3.

= 3x²y

Step 3: Square y, multiply by x, then multiply by 3.

= 3xy²

Step 4: Cube y.

= y³

Step 5: Combine your initial answers and reduce if necessary.

= x³ + 3x²y + 3xy² + y³

Answer:

The cube of the binomial ( x + y ) or ( x + y ) ³ is

= x³ + 3x²y + 3xy² + y³